2020
DOI: 10.1029/2019je006241
|View full text |Cite
|
Sign up to set email alerts
|

The Extraterrestrial Dust Flux: Size Distribution and Mass Contribution Estimates Inferred From the Transantarctic Mountains (TAM) Micrometeorite Collection

Abstract: This study explores the long‐duration (0.8–2.3 Ma), time‐averaged micrometeorite flux (mass and size distribution) reaching Earth, as recorded by the Transantarctic Mountains (TAM) micrometeorite collection. We investigate a single sediment trap (TAM65), performing an exhaustive recovery and characterization effort and identifying 1,643 micrometeorites (between 100 and 2,000 μm). Approximately 7% of particles are unmelted or scoriaceous, of which 75% are fine‐grained. Among cosmic spherules, 95.6% are silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 68 publications
1
39
2
Order By: Relevance
“…Evidence of stable flight histories includes cumulative settling of dense phases such as olivine and/or metal beads (Genge et al 2016), the floating of low‐density phases (i.e., vesicles) away from the particle’s leading front (Genge et al 2017), and the preservation of a coherent remnant magnetic field on cooling below the curie point (Suavet et al 2011). Spinning cosmic spherules appear rarer but are evidenced by hollow spherules containing a single large off‐center void (Suavet et al, 2011; Suttle and Folco 2020). Spinning dust is likely to be immature, that is, recently released from their parent asteroid, and because their rotation rates have not been yet dampened by magnetic effects (Genge 2017b), while particles with stable orientations are likely older dust, released a long time ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of stable flight histories includes cumulative settling of dense phases such as olivine and/or metal beads (Genge et al 2016), the floating of low‐density phases (i.e., vesicles) away from the particle’s leading front (Genge et al 2017), and the preservation of a coherent remnant magnetic field on cooling below the curie point (Suavet et al 2011). Spinning cosmic spherules appear rarer but are evidenced by hollow spherules containing a single large off‐center void (Suavet et al, 2011; Suttle and Folco 2020). Spinning dust is likely to be immature, that is, recently released from their parent asteroid, and because their rotation rates have not been yet dampened by magnetic effects (Genge 2017b), while particles with stable orientations are likely older dust, released a long time ago.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 22 giant MMs with sizes between 29 × 10 6 µm 3 and 116 × 10 6 µm 3 (see Table 1). They were collected by the PNRA (Programma Nazionale di Ricerca in Antartide) from an MM trap on the top of Miller Butte in the Transantarctic Mountains (Folco et al 2008; Rochette et al 2008; Suttle and Folco 2020). The processes of alteration experienced during their up to 1–2 million years long stay on Earth have been studied by Suavet et al (2009, 2011) and Van Ginneken et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…They are therefore a major component of the near-Earth dust complex in agreement with isotopic statistics [80]. Coarse-grained micrometeorites, which are primarily fragments of chondrule, and CAI (Ca-and Al-rich inclusions) represents a smaller component (< 25%) of the micrometeorite flux [81,91]. Thus, the major constituent minerals are olivine, low-Ca pyroxene, magnetite, sulfides, metal, and hydrous Fe-Mg silicates like serpentine and saponite.…”
Section: The Interplanetary Dust Complexmentioning
confidence: 54%
“…If astronomical observations carried out by the Infrared Astronomical Satellite (IRAS) and Cosmic Background Explorer (COBE) satellites in the 1980s indicated that collisions in the main asteroid belt (MAB) are the dominant source of dust in the near-Earth space [78], dynamical simulations predict in turn that the bulk of the Zodiacal cloud can be best produced by debris derived from Jupiter family comets (JFCs) through spontaneous disruption [79]. Oxygen isotopic data from relatively large micrometeorites in the 100-1000 µm size range collected at the Earth's surface [80][81][82] indicates that the interplanetary dust complex is dominated by dust produced by cometary activity and by collisions between primitive hydrous asteroids of carbonaceous chondrite compositions, with a subordinate contribution from more evolved anhydrous asteroids (mainly ordinary chondritic and Vesta-like). An additional small fraction of micrometeorites, with heavy oxygen isotope composition, may sample an unknown body in the solar system, namely a body not yet sampled by macroscopic meteorites.…”
Section: The Interplanetary Dust Complexmentioning
confidence: 99%
See 1 more Smart Citation